A-04 Acute Sports-Related Concussion Associations Between Cognitive Symptoms, Memory Performance, and Default Mode Network Hub Connectivity. (13th July 2022) - Bouchard, H C; Schultz, D H; Higgins, K; Laing, J M; Rodriguez, A I; Carlson, E; Tuttle, J; Mayer, M; Albers, L; Maerlender, A; Neta, M; Savage, C R
Abstract: Purpose: Disruptions in cognitive performance are commonly reported after a sports-related concussion (SRC) and may be related to brain network changes, particularly within the default mode network (DMN). Since well-connected brain regions across networks (hubs) play an important role in network organization, we hypothesize that DMN hubs will be disrupted after a SRC and associated with cognitive symptoms and cognitive performance. Methods: We collected resting-state fMRI, symptoms, and cognitive performance data from 44 student-athletes at baseline, after a SRC, and at recovery. Participation coefficient defined hubs for each athlete. We compared changes in functional connectivity between hubs and non-hubs within the DMN and between DMN hubs and non-hubs in the remaining networks. We used linear regression to examine the relationship between functional connectivity, cognitive symptoms, and cognitive performance while controlling for concussion history. Results: Functional connectivity between hubs and non-hubs within the DMN increased from baseline to post-injury and decreased from post-injury to recovery, but not to baseline connectivity levels. Post-injury functional connectivity was related to increased cognitive symptoms and decreased visual memory performance. Functional connectivity decreased between hubs in the DMN and non-hubs in the cingulo-opercular, salience, somatomotor, and visual networks from baseline to post-injury. Cognitive symptoms and visual memory performance were related to functional connectivity between DMN hubs and visual network non-hubs. Conclusions: Self-reported cognitive symptoms and cognitive performance were associated with changes in DMN hub connectivity. This relationship may suggest a decrease in efficiency between brain networks after a SRC and may provide insight into post-injury compensation during task performance.